Copper‐Exchanged Omega (MAZ) Zeolite: Copper‐concentration Dependent Active Sites and its Unprecedented Methane to Methanol Conversion. Issue 24 (26th November 2018) - Knorpp, Amy J.; Pinar, Ana B.; Newton, Mark A.; Sushkevich, Vitaly L.; van Bokhoven, Jeroen A.
Abstract: The direct conversion of methane to methanol may provide a way to utilize methane that is otherwise wasted. Here we have explored one of the most promising copper zeolite materials to date, copper‐exchanged omega (MAZ ) zeolite. With highly crystalline and uniform zeolite omega, we can produce 150 umol‐methanol/gram‐zeolite under 1 bar methane and as high as 200 umol‐methanol/gram‐zeolite under 30 bar methane, the highest yield ever reported. Furthermore, zeolite omega's ability to convert methane to methanol has a distinct copper‐concentration dependent behavior. At lower copper loadings, Cu–MAZ is inactive, and once a minimum copper loading is reached, Cu–MAZ converts methane to methanol more selective than the widely studied Cu‐mordenite. With the unprecedented high conversion and selectivity, Cu–MAZ provides insight into the active copper phase and its mechanism which was quantified as two electrons per molecule of methanol produced. Abstract : Alpha and Omega ! One of the most promising copper zeolite materials to date is explored for the direct conversion of methane to methanol, copper‐exchanged omega (MAZ ) zeolite. At lower copper loadings, Cu–MAZ is inactive, and once a minimum copper loading is reached, Cu–MAZ converts methane to methanol with remarkable selectivity and an unprecedented methanol yield which allowed for the determination of the mechanism as a two‐electron process.